Management of Local Culture-Based Education Curriculum in Taman Indria-IPTs Kindergarten and Pedagogia Laboratory Kindergarten - Ikhsanul Azizah; Tina Rahmawati; Asa Ismia Bunga Aisyahrani (Yayasan Keluarga Guru Mandiri, 2025)
This study analyzes the management of a local culture-based curriculum in TK Taman Indria-IPTs and TK Laboratorium Pedagogia, focusing on curriculum planning, organization, implementation, and evaluation. Using a qualitative research method with a case study approach, data were collected through interviews, observations, and documentation. Data validity was ensured using internal validity techniques, and analysis was conducted using Yin's (2018) model, which includes pattern matching and explanation building. The findings reveal that curriculum planning involves setting objectives, selecting learning media, and incorporating culturally relevant teaching methods. The organization stage includes developing programs, academic calendars, and lesson schedules. The implementation phase integrates cultural content into school-wide and classroom activities, emphasizing school culture, habituation, and cultural practices. Curriculum evaluation is conducted systematically, with TK Laboratorium Pedagogia applying large- and small-scale evaluations, while TK Taman Indria-IPTs employ internal and external evaluations. Supporting factors include effective communication between schools and parents, community involvement, and a supportive cultural environment, while challenges include diverse student backgrounds, teacher workload, and limited infrastructure. This study contributes to developing educational management theories by providing a framework for managing culture-based curricula, offering insights that can guide early childhood education institutions in implementing culturally responsive learning environments.